Mainstreaming of Lampung Coffee Drinking Day as Contributor to Global Environmental Security Achievements: Pengarusutamaan Hari Minum Kopi Lampung sebagai Kontributor Pencapaian Keamanan Lingkungan Global - Jaya Winata, Indra; Sulistyo, Iwan; Karisma, Gita (Ragom Jurnal Pengabdian Masyarakat, 2023)
Environmental problems have occurred since the global industry began to progress. Security issues are shifting from traditional security to non traditional security involving environmental issue which have been experienced by all countries at this time. The haze from burning energy around the world is a major contributor to environmental pollution and global warming. Reduction of green land for the industrial sector causes wider effect for environmental security. From these problems, the solutions could be coming from Subnational actors who may potentially support global environmental security. The role of sub-national is needed to encourage various program related to coffee plantation which eventually support environmental sustainability. The large demand for coffee can encourage the planting of more coffee plants and garden shaders, so that the clearing of green land becomes more massive. From these efforts, environmental improvements can be achieved. This Community Service activity uses the method of delivering material from two sources, coffee activists and scholars